Comprehension of creativity in the context of the correlation of Plato’s philosophy, theories of fractals and archetypes - Stoletov, Anatoliy (Creativity Studies, 2022)
The study examines the creative process using the logical and methodological analysis of Plato’s concepts. It presents the modern scientific research related directly or indirectly to his philosophical views (the structural analogy method, the theory of archetypes and fractals and many others). A number of modern studies and concepts, such as the theory of fractals, evolutionary epistemology, the concept of autopoiesis, and others, confirm Plato’s views on the structure of the world and creativity. For this reason, the authors define creativity as the activity of a rational and social subject to produce a qualitatively new thing based on universal patterns of the fractal and archetype nature in accordance with the ideal. This activity needs in creativeness which is the state of love as a creative force arising from social interaction as a desire to create and expand space for life, connecting space inside the subject of creativity and outside it, creating a resonance between the creative self and other persons.